Investigation on Surface Roughness of Polyimide Film from Vapour Deposition Polymerization - Yao, Hong; Li, Sai; Qi, Xiao-Bo; Huang, Yong; Zhang, Wen-Zhan (Asian Journal of Chemistry, 2012)
Polyimide film is an important candidate as an ablator material for inertial confinement fusion targets due to its superior mechanical and thermal properties. During the centripetal blast of the inertial confinement fusion ignition experiment, the roughness would have great effect on the hydrodynamic instabilities. Many inertial confinement fusion experiments exploit controlled variations in initial capsule roughness. This paper mainly presented the investigation on the surface roughness of polyimide film from vapour deposition polymerization. Polyimide films of pyromellitic dianhydride-oxydianiline (PMDA-ODA) were fabricated by vapour deposition polymerization method at high vacuum pressure of 10-4 Pa. The effects investigated on the surface roughness include: equipment adjustments, substrate temperature, heating pattern and the monomers deposition rate ratio. Surface morphology of the films was characterized by an interferometer microscopy and scanning electron microscopy. Surface roughness was measured by an atomic force microscopy. The results show that consecutive film can be fabricated at the optimal source-substrate distance of 74 mm. Surface roughness for one-step heating and segmented heating process were 291.2 and 61.9 nm, respectively. Splash of solids can be effectively avoided by adopting a fine mesh. A film with surface roughness of 3.3 nm was obtained when pyromellitic dianhydride and oxydianiline deposition rate ratio was set at 0.9:1. Setting the substrate temperature at 30 ºC is in favour of forming a planar film. The authors then concluded that high-quality film satisfying with inertial confinement fusion experiment can be fabricated by vapour deposition polymerization method.